Penerapan Analisa PIECES dan Rancang Bangun Sistem Informasi Inventaris Kantor dengan Pemodelan UML Berbasis Website - Anang Maulana; Agus Budiyantara (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
An information system is an integration between information technology and human activities that play a role in the management, processing, and dissemination of information within an organization or a particular environment. Along with technological advances, website-based information systems have become an effective solution for companies in managing office inventory more efficiently and structured. This research focuses on the design of a website-based office inventory information system aimed at simplifying the performance of admins in the inventory data management process. However, this matter has weaknesses in its management such as still using Microsoft Excel so it is vulnerable to malware if employees want to request the data with a USB that becomes a corrupt file and the occurrence of inventory management errors that cause differences between the actual conditions or human error. Before designing the system, an analysis of the existing inventory mechanism was conducted using the PIECES approach (Performance, Information, Economy, Control, Efficiency, and Service) to evaluate the performance of the old system and identify improvement needs. In addition, system modeling was carried out using the Unified Modeling Language (UML) through use case diagrams, activity diagrams, and class diagrams. The final result of this research is an efficient and integrated website-based office inventory information system.